The Effect of Additional Ethanol Steam Temperature Variations on Pertalite Fuel Use on Performance and Efficiency of 4 Stroke Motorcycles - Akhmad Saifudin (Procedia of Engineering and Life Science, 2021)
The means of transportation that are widely used in Indonesia are vehicles in the form of motorbikes and cars, as well as the increasing dependence on the consumption of fuel oil (BBM). The impact is that the need for fuel oil is also high. As a result of dependence on fossil energy this one increases. Based on the problems that have been raised, a concept has emerged to make alternative fuels that can be used as a fuel mixture or as an alternative to these fuels. One of the renewable energy sources that can be utilized is ethanol which comes from corn, wheat, and others. ethanol vapor as a fuel mixture, where the ethanol used is not mixed directly into the fuel. And by utilizing ethanol vapor, it is also expected to increase the performance and efficiency of motorbikes. In this study we used a reference concept which was then used as a concept, how to influence additional ethanol vapor temperature variations on the use of pertalite fuel on the performance and efficiency of 4-stroke motorbikes using temperature variations of 400C, 500C, and 600C and variations of valve openings on the ethanol vapor hose to the intake manifold. After conducting the test, the results show that the best power is obtained from the addition of ethanol steam at a temperature of 450 full openings when it is at 7973 RPM rotation which shows a power of 31.2 HP and when it is at 5757 RPM rotation which shows a torque of 32.24 N.m. The best fuel efficiency is obtained from the addition of ethanol steam with a temperature of 450 full openings with a fuel consumption of 1 liter only reduced by 75 ml every 5 minutes of use at the same speed.